Comparison between different diagnostic tests used for bacterial vaginosis - Vasundhara, Vasundhara; Farooq, Umar; Najam, Rehana (Tropical Journal of Pathology and Microbiology, 2019)
Background: Bacterial vaginosis is the primary reason for unusual vaginal expulsion in females of fertile age resulting in poor pregnancy ending, pelvic seditious disease, chorioamnioitis, endometritis and increased susceptibility to HIV.As the prevalence is high, and usual investigative tests require laboratory expertise, a future study was therefore performed to compare different diagnostic methods for making an precise diagnosis of bacterial vaginosis. Materials and Methods: This study was conducted in Department of Microbiology which included females of reproductive age group, attending Obstetrics and Gynaecology OPD of TMMC & RC, Moradabad, over a period of one year (March 2017- March 2018). A total of 400 patients with complaints of vaginal discharge and other associated complaints like pruritus, pain lower back, primary or secondary infertility were included in the study. Diagnosis of Bacterial vaginosis was done by using an array of both conventional techniques which included Gram’s staining, Nugent’s score, vaginal pH etc., and a newer diagnostic technique (OSOM BV Blue test). The patients were also examined PV and the relevant clinical findings were also noted. Results: Out of a total of 400 patients listed for the study, 240 were diagnosed as having bacterial vaginosis. Comparison of the different methods for the diagnosis of bacterial vaginosis revealed that bacterial vaginosis could be detected by ‘clue cells’ in 100% patients, by OSOM BV Blue test in 97.6% patients, by Amsel’s criteria in 67.1% patients, and by evaluation of vaginal pH and vaginal amines in 63.4% and 62.2% patients respectively. Conclusion: Different diagnostic techniques have varied sensitivity and specificity in diagnosis of bacterial vaginosis. OSOM B.V. blue test is found to be highly sensitive and can be performed easily in clinical settings where microscopic facilities are not available.